Long-term Likelihood of Patch Testing, Academic Practice, and American Contact Dermatitis Society Membership Among North American Alexander Fisher Award Winners From 1989 to 2012. Issue 6 (November 2018) - Hamann, Dathan; Taylor, James S.
Abstract : Background: The Alexander Fisher Award (AFA) recognizes excellence in research among dermatology residents or medical students who make formal presentations at the annual American Contact Dermatitis Society (ACDS) meeting. Objective: The aim of the study was to investigate long-term likelihood of patch testing, academic practice, and society membership among Alexander Fisher Award winners (AFAWs). Methods: The AFAWs from 1989 to 2012 were identified with Internet searches to obtain their current practice location. Each practice was contacted by phone, and staff was asked whether the AFAW performed patch testing. Current ACDS membership was confirmed by ACDS leadership. Academic status was assessed by university association on practice Web sites. Results: Sixty-two awards were presented to 60 individuals from 1989 to 2012. Fifty AFAWs are actively practicing dermatology in the United States (n = 43) and Canada (n = 7). Of 50 practicing AFAWs, 18 (36%) are active patch testers, 29 (58%) do not perform patch testing, and 3 (6%) could not be reached or staff declined to answer. Of the 50, 14 (28%) practice in an academic setting, and 10 (20%) are current ACDS members.